Kelemahan Inspektorat Daerah dan Ketidakpatuhan Ketentuan Perundang-undangan Pada Praktek Audit Pemerintah Daerah di Indonesia - Susanto, Heri (STIE Surakarta, 2015)
This study developed astatistical model of non-complian cereporting provisions of law and control of the Inspectorate findings BPK audit opinion. The purpose of this study was to analyze the factors that affect the out come of the Supreme Audit Agency audit opinion received by the local government. This study has selected 371 samples to the local government for the year 2014. Research using financial statement data in the formof government in 2014 soft copy of the Supreme Audit Agency and other publications. The results showed that non compliance reporting provisions of low and Inspektorat control weakness, has significant effect on the administration of the BPK audit opinion.